Zincke-derived viologen covalent organic framework as a high-performance cathode for aqueous zinc-iodine batteries - Das, Gobinda; Shivade, Rajkiran; Pandey, Priyanshi; Varghese, Sabu; Rajput, Nitul; Matouk, Zineb; Martinez, Jose Ignacio; Straubinger, Rainer; Benyettou, Farah; Gandara, Felipe; Olson, Mark A.; Aouad, Samer; et al. (Small, 2025)
Aqueous zinc-iodine (Zn-I2) batteries are among the most promising energy storage technologies, offering high energy density, low cost, and intrinsic safety. However, their practical deployment is hindered by the polyiodide shuttle effect, leading to rapid capacity fading and poor cycling performance. This work demonstrates the application of a crystalline viologen-based covalent organic framework (TAB-DNP-BP COF), synthesized via a one-pot Zincke reaction, as an efficient iodine host material. The cationic backbone of the TAB-DNP-BP COF effectively confines iodine (I2) species and electrostatically traps polyiodides, suppressing their migration and protecting the zinc anode. Zinc-iodine batteries assembled with an I2-enriched TAB-DNP-BP COF (TAB-DNP-BP COF@I2) cathode deliver a high specific capacity of 337 mAh g-1 at 0.5 C, surpassing the performance of most reported COF-, MOF-, and cage-based systems, while exhibiting excellent cycling stability over 5000 cycles. This work highlights the potential of ionic COFs for stabilizing iodine chemistry and offers a promising strategy toward the development of high-performance, durable aqueous Zn-I2 batteries.
Keywords: iCOF; iodine confinement; viologen; zinc-iodine batteries; Zincke reaction